2021
DOI: 10.1038/s41386-021-00976-w
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic neuroimaging to study the dose-related brain kinetics and target engagement of buprenorphine in vivo

Abstract: A wide range of buprenorphine doses are used for either pain management or maintenance therapy in opioid addiction. The complex in vitro profile of buprenorphine, with affinity for µ-, δ-and κ-opioid receptors (OR), makes it difficult to predict its dose-related neuropharmacology in vivo. In rats, microPET imaging and pretreatment by OR antagonists were performed to assess the binding of radiolabeled buprenorphine (microdose 11 Cbuprenorphine) to OR subtypes in vivo (n=4 per condition). The µ-selective antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 61 publications
4
14
0
Order By: Relevance
“…Twelve rats were administered pure AMX in a 0.25% CMC suspension, and the remaining 12 were given an equivalent dose of AMX-SLNs (4 mg/kg). The animals were sacrificed at each pharmacokinetic point: 0.5, 1.5, 2.5, 3, and 6 h, with the brain samples collected in phosphate-buffered saline at pH 7.4 and stored at −20 °C until further analysis. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve rats were administered pure AMX in a 0.25% CMC suspension, and the remaining 12 were given an equivalent dose of AMX-SLNs (4 mg/kg). The animals were sacrificed at each pharmacokinetic point: 0.5, 1.5, 2.5, 3, and 6 h, with the brain samples collected in phosphate-buffered saline at pH 7.4 and stored at −20 °C until further analysis. , …”
Section: Methodsmentioning
confidence: 99%
“…The animals were sacrificed at each pharmacokinetic point: 0.5, 1.5, 2.5, 3, and 6 h, with the brain samples collected in phosphate-buffered saline at pH 7.4 and stored at −20 °C until further analysis. 59…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…11 C-Buprenorphine was synthesized in-house according to the method described by Lever et al 28 with minor modifications previously described. 26 Ready-to-inject 11 C-buprenorphine (1.8-3.5 GBq, decay-corrected radiochemical yield: 15%) was obtained with a radiochemical purity above 98% and a molar activity of 28 GBq/lmol at end of synthesis (EOS). 11 C-Flumazenil was synthesized based on a previously published method.…”
Section: Chemicals and Radiochemicalsmentioning
confidence: 99%
“…25 We recently validated 11 C-buprenorphine in rodents and non-human primates as a mean to specifically address the neuropharmacokinetics and binding of buprenorphine to its CNS targets in vivo. 26,27 Blocking experiments performed in rats suggested that the specific binding of 11 Cbuprenorphine in the brain predominantly corresponds to its interaction with MORs rather than with other OR subtypes. 26 In the present study, the hypothesis of a mutual DDI between buprenorphine and diazepam, a widely used benzodiazepine, was investigated at the neuroreceptor level using brain PET imaging, according to a cross-over design in non-human primates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation